Description of alveolar bone resorption in partially edentulous mandible of a female patient in panoramic radiograph - Firas A. Khairinisa; Azhari; Farina Pramanik (DiscoverSys Inc., 2022)
Objective: The purpose of this research was to determine alveolar bone resorption by measuring alveolar bone height in the mandible of partially edentulous female patients through panoramic radiograph Material and Methods: The method of this study was descriptive using 34 panoramic radiographs of partially edentulous mandible in female patients aged 20-45 years in Dental Radiology Installation of Unpad Dental Hospital from 2016 to 2017. Alveolar bone height was measured using Proximal RABL (Radiographic Alveolar Bone Loss) method with the help of Ez-Pax Plus software. Results: The highest average alveolar bone height was 3.5 mm and 12.96% of them occurred in 30-35 years age group. The lowest height was 3 mm with 10.98% occurred in 20-29 years age group. Conclusion: Alveolar bone height in partially edentulous mandible of female patients underwent resorption of mild classification according to proximal RABL method.